Rape Cases Legal Aspects of Higher Education Involvement in Mineral and Coal Mining Agglomerations in Indonesia - Hasan, Bob (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
Mineral and coal mining agglomerations (minerba) in Indonesia have become an economic strategy to improve the efficiency and competitiveness of the extractive industry. In its development, Law Number 3 of 2020 concerning Mineral and Coal Mining authorizes state universities to manage Special Mining Business Areas (WUPK). The involvement of universities in mining agglomerations has various legal and economic implications, including licensing, governance, and environmental and social impacts. This article analyzes the legal framework governing the role of universities in mining management and examines the effectiveness of regulations in supporting sustainable economic growth. Through a normative approach and policy analysis, this study finds that although regulations have opened opportunities for universities to participate in the mining industry, challenges remain in terms of regulatory harmonization, oversight mechanisms, and the balance between academic interests and the commercialization of natural resources. The Fourth Amendment to Law Number 4 of 2009 concerning Mineral and Coal Mining aims to restore and revitalize the spirit of Article 33 of the 1945 Constitution by involving universities, which are expected to contribute to innovation, increasing the added value of minerals and coal, and the sustainability of the national economy. Furthermore, this also serves as an important momentum to improve mining governance to be more environmentally conscious and equitable. Granting mining management permits to universities can be an effort to overcome the funding limitations faced by universities, especially in the development of research and innovation